2013
DOI: 10.7448/ias.16.1.18560
|View full text |Cite
|
Sign up to set email alerts
|

Never tested for HIV in Latin‐American migrants and Spaniards: prevalence and perceived barriers

Abstract: IntroductionIncreasing the uptake of HIV testing and decreasing the number of undiagnosed people is a priority for HIV prevention. Understanding the barriers that hinder people from testing is vital, particularly when working with especially vulnerable populations like migrants. Most data available on migrants are based on African migrants in the UK, while barriers to HIV testing in Latin-American migrants living in Europe remain unexplored. Still, they account for a quarter of new diagnosis in Spain and suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 26 publications
(28 reference statements)
6
42
0
6
Order By: Relevance
“…Feeling healthy, lack of symptoms, and lack of preventive healthcare were barriers to HIV testing across the board [8,11,16,28,41,51,52]. It was identified that African migrants' contact with traditional medicine in their home country was usually greater than that with western medicine, and this acted as a barrier in the receiving country [52].…”
Section: Knowledge Attitudinal and Behaviouralmentioning
confidence: 97%
See 1 more Smart Citation
“…Feeling healthy, lack of symptoms, and lack of preventive healthcare were barriers to HIV testing across the board [8,11,16,28,41,51,52]. It was identified that African migrants' contact with traditional medicine in their home country was usually greater than that with western medicine, and this acted as a barrier in the receiving country [52].…”
Section: Knowledge Attitudinal and Behaviouralmentioning
confidence: 97%
“…Research on migrants in Australia, the US, Canada and Europe highlight migrants' vulnerability to HIV, with rates exceeding those of the general host population [7][8][9][10][11][12]. A striking example of this comes from Belgium where, between 2002 and 2006, figures showed that, despite accounting for \1 per cent of the population, migrants from Sub-Saharan Africa accounted for nearly half (45.7 per cent) of newly diagnosed cases of HIV [11].…”
Section: Introductionmentioning
confidence: 98%
“…It has been hypothesized that in the process of deciding and taking the test, psychosocial factors interact with health system variables [8]. Some barriers to testing pointed out in several studies, besides those related to the perception of not having been at risk for infection and the fear of dealing with the disease and the social consequences of a positive result [9,10], could be related to characteristics of the diagnostic services, such as the need and anxiety created by having to return for a second visit to find out the result [8][9][10][11][12], knowing where to go [11], finding a place to get tested [11], the inconvenience of having to visit health services for testing during working hours [12], embarrassment about testing [11], discomfort about talking to health workers about sex life [13], avoidance to go through counselling [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, this could not be ascertained as we have not found any similar pharmacy-based programmes in which testing was offered free of charge. Nevertheless, recent studies show that money is not a major barrier when deciding to be tested for HIV [37]. Also, we were unable to perform a proper cost−benefit analysis but, according to some studies, the programme can be deemed to be cost-effective as we identified more than 1 undiagnosed person per 1000 tests performed [38,39].…”
Section: Discussionmentioning
confidence: 94%